Eye Drops of Metformin Prevents Fibrosis After Glaucoma Filtration Surgery in Rats via Activating AMPK/Nrf2 Signaling Pathway - Li, Xueru; Leng, Yu; Jiang, Qingzhi; Wang, Ziwen; Luo, Peng; Zhang, Chi; Chen, Long; Wang, Yawei; Wang, Huilan; Yue, Xiaofeng; Shen, Chongxing; Zhou, Yuanlinhan; et al. (Frontiers in Pharmacology, 2020)
Metformin is a widely used hypoglycemic agent to treat type 2 diabetes (DM2). There is growing evidence that metformin has an effective therapeutic effect in anti-tumor and anti-fibrotic diseases. However, it is not clear how the antifibrotic effect of metformin in the eye and how it is transferred. Here, the effects of topical metformin treatment were studied in Sprague-Dawley (SD) rats of glaucoma filtrating surgery (GFS). Rats were administered randomly bilateral drops: control group (without surgery), GFS group, metformin group or mitomycin C (MMC) group (sponge application intraoperatively, 0.02%). Bleb features and intraocular pressure (IOP) were assessed for postoperative week 4. Metformin effectively reduced fibrosis and prolonged bleb survival in SD rats GFS model. Further in vitro tests showed that the levels of fibrosis and oxidative stress in metformin treated-Human Conjunctival Fibroblasts (HConFs) were significant decreased, and the pro-fibrotic response of HConFs were decreased by inducing macrophagic polarity changes. In addition, the competition of organic cation transporters (OCTs) and the inhibition of nuclear factor erythroid 2-related factor 2 (Nrf2) or AMP-activated protein kinase (AMPK) reversed the anti-fibrotic effects of metformin. Together, the study suggests that metformin enters into HConFs cell with OCTs, which protect against filtrating blebs scar information in SD rats of GFS via activating the AMPK/Nrf2 axis and the downregulation of profibrogenic and inflammatory biomarkers.